Lagenorhynchus Gray 1846 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lagenorhynchus Gray 1846 Lagenorhynchus Gray 1846, Ann. Mag. Nat. Hist., ser. 1, 17: 84. Type Species: Delphinus albirostris Gray 1846 Synonyms: Electra Gray 1866; Leucopleurus Gray 1866; Sagmatius Cope 1866. Species and subspecies: 6 species with 2 subspecies: Species Lagenorhynchus acutus (Gray 1828) Species Lagenorhynchus albirostris Gray 1846 Species Lagenorhynchus australis Peale 1848 Species Lagenorhynchus cruciger (Quoy and Gaimard 1824) Species Lagenorhynchus obliquidens Gill 1865 Species Lagenorhynchus obscurus (Gray 1828) Subspecies Lagenorhynchus obscurus subsp. obscurus Gray 1828 Subspecies Lagenorhynchus obscurus subsp. fitzroyi Waterhouse 1838 Discussion: Reviewed by Fraser (1966). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 729, DOI: 10.5281/zenodo.7316519